Megakaryocytes in pleural and peritoneal fluids: prevalence, significance, morphology, and cytohistological correlation. Issue 12 (December 1980) - Kumar, N B; Naylor, B
Abstract : Over a period of 22 years, 4844 pleural and peritoneal fluids from 3279 patients were examined cytologically. Megakaryocytes were found in the fluids from five patients. The clinical diagnoses in the five patients were agnogenic myeloid metaplasia, chronic myeloid leukaemia, and lymphocytic lymphoma. All of these patients had persistent serous effusions. Megakaryocytes in serous fluids occurred in three forms: (1) a large type with abundant cytoplasm and multilobed nuclei, (2) a smaller type with a high nucleocytoplasmic ratio and unlobed nuclei, and (3) anucleate cytoplasmic masses. Foci of agnogenic myeloid metaplasia found on the serous surfaces at necropsy of two patients contained megakaryocytes similar to those in the corresponding effusions. The clinical course of our patients confirmed that the presence of megakaryocytes in serous fluids signifies an advanced haematopoietic malignancy.